FARMERS’ LIVELIHOODS STRATEGY BASED ON ASSET IN PANDANSARI VILLAGE POST ERUPTION OF MOUNT KELUD - Abraham Ruylthon Illu; Abdul Wahib Muhaimin; Budi Setiawan (Socio-Economics/Agribusiness Department, 2021)
This study examines farmers' livelihood strategies based on livelihood assets in Pandansari Village, Ngantang District, Malang Regency. This study uses a quantitative descriptive approach using a Likert scale. Primary data were obtained through in-depth interviews using questionnaires and field observations, while secondary data were obtained through literature studies from various related sources. The location was determined purposively with the consideration that Pandansari Village was the area in Ngantang District that was the worst affected by the eruption of Mount Kelud. Seventy-five farmers with simple random sampling technique were selected as respondents in this study. The respondents' livelihood assets include human capital, natural capital, social capital, financial capital, and physical capital. Meanwhile, livelihood strategies are classified into survival strategies, consolidation strategies and accumulation strategies. The results show that the most vital livelihood asset is social capital, while the indicator for natural capital is the weakest. The strongest indicator of the farmer's livelihood strategy in Pandansari Village is the consolidation strategy.